Approximating the Inverse of a Square Matrix with Application in Computation of the Moore-Penrose Inverse - F. Soleymani; M. Sharifi; S. Shateyi (Journal of Applied Mathematics)
This paper presents a computational iterative method to find approximate inverses for the inverse of matrices. Analysis of convergence reveals that the method reaches ninth-order convergence. The extension of the proposed iterative method for computing Moore-Penrose inverse is furnished. Numerical results including the comparisons with different existing methods of the same type in the literature will also be presented to manifest the superiority of the new algorithm in finding approximate inverses.